Key role of rotated domains in oxygen intercalation at graphene on Ni(1 1 1). (22nd May 2017) - Bignardi, Luca; Lacovig, Paolo; Dalmiglio, Matteo M; Orlando, Fabrizio; Ghafari, Aliakbar; Petaccia, Luca; Baraldi, Alessandro; Larciprete, Rosanna; Lizzit, Silvano
Abstract: Herein, we provide a complete description of the intercalation of oxygen at the strongly interacting graphene on Ni(1 1 1), highlighting the role of rotated graphene domains in triggering the intercalation. High-resolution core-level photoelectron spectroscopy provided a full characterization of the interface at each stage of the intercalation, revealing the formation of an oxide layer between graphene and the metal substrate. Angle-resolved photoemission spectroscopy measurements showed that the oxide decouples efficiently graphene from the substrate, restoring the Dirac cone and providing a slight n -doping. Photoelectron diffraction experiments revealed that graphene domains not aligned with the Ni substrate are the first to be intercalated with oxygen and are preferential regions under which the oxygen is retained during the deintercalation.